Respuesta :

Answer:

-6/5, 0, 6/5

Step-by-step explanation:

  1. First factor out the d and you are left with d(25d^2-36)=0
  2. (a+b)(a-b) = a^2-b^2
  3. Using that principle you can then simplify further by factoring it into d(5d+6)(5d-6)=0
  4. Then just solve to get the answers.

Answer:

-6/5, 0, 6/5.

Step-by-step explanation:

25d3 – 36d = 0

The GCF is d so we have:

d(25d^2 - 36) = 0

d = 0 is one solution, and:

25d^2 - 36 = 0

25d^2 = 36

d^2 = 36/25

d = +/- 6/5

d = -6/5, 6/5.

ACCESS MORE